ECO-AESTHETICS GREEN PANEL PADA BANGUNAN RUMAH TINGGAL - Wiwiek Dwi Serlan; Andi Gunawan; Bambang Sulistyantara (Jurnal Lanskap Indonesia, 2013)
ABSTRACTGlobal climate changing and air condition warming has affect human thermal comfort quality. In 1961-1990 period, Indonesia ambient temperature increased to ± 0.5 ºC. It was projected that the temperature increase about 1.8 to 4.0 ºC in 2000-2050. In a fact, Indonesia comfortable temperature is about 27-28 °C. That comfortable can be created by natural elements such as plants. However, the problems of urban settlement is land limitation and land economic value. Plants presence like green open space was difficult to maintain in urban area. So the solution is made plant procurement by verticultur techniques, for example green panel. Green panel has function as secondary skin (second layer) to protect building from direct solar radiation, and also create comfortable micro climate inside building.The aims of this study was created standard criteria of green panel for house building base on eco-aesthetic principles. This study used calculation of temperature decreasing to evaluate green panel effect. Scenic Beauty Estimation (SBE) and Semantic Differential (SD) was used to assess green panel visual quality. Parameters tested of this study were distance of plant placed and plant types. The best plant combination of green panels are Cuphea hyssopifolia and Iresine herbstii which were placed on 0-50 cm distance from residential buildings walls.Keywords: green panel, eco-aesthetic, thermal comfort, house building.